2016
DOI: 10.3899/jrheum.150996
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Cells in Diffuse Cutaneous Systemic Sclerosis Overexpress Activated ADAM12 and Are Involved in Myofibroblast Transdifferentiation and Development of Fibrosis

Abstract: Objective.Microvascular damage is pivotal in the pathogenesis of systemic sclerosis (SSc), preceding fibrosis, and whose trigger is not still fully understood. Perivascular progenitor cells, with profibrotic activity and function, are identified by the expression of the isoform 12 of ADAM (ADAM12) and this molecule may be upregulated by transforming growth factor-β (TGF-β). The goal of this work was to evaluate whether pericytes in the skin of patients with diffuse cutaneous SSc (dcSSc) expressed ADAM12, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…The neutrophils of the intraluminal thrombus exposed to tobacco smoke extract showed increased ADAM10 and 17 content, cleavage of these molecules into active forms, and release of membrane microvesicles carrying mature ADAM10 and detectable ADAM17, which contributed to the damage of the underlying aortic wall [38]. As might be expected, we found that both ADAM10 and ADAM17 proteins were upregulated in the murine AAA in the current study, which is similar to the previous observation that both transmembrane proteases are also elevated in the rat thoracic aortic aneurysm [39]. The data also offer new experimental support for the involvement of ADAM10 in the development of AAA, consistent with previous study [14].…”
Section: Discussionsupporting
confidence: 90%
“…The neutrophils of the intraluminal thrombus exposed to tobacco smoke extract showed increased ADAM10 and 17 content, cleavage of these molecules into active forms, and release of membrane microvesicles carrying mature ADAM10 and detectable ADAM17, which contributed to the damage of the underlying aortic wall [38]. As might be expected, we found that both ADAM10 and ADAM17 proteins were upregulated in the murine AAA in the current study, which is similar to the previous observation that both transmembrane proteases are also elevated in the rat thoracic aortic aneurysm [39]. The data also offer new experimental support for the involvement of ADAM10 in the development of AAA, consistent with previous study [14].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, immunohistochemistry studies performed two decades ago suggested that subsets of perivascular mesenchymal cells migrate from their perivascular location and become myofibroblasts, synthesizing collagen in patients with excessive dermal scarring (88). Consistent with this hypothesis, increased numbers of PDGFRβ + perivascular cells are found in patients with early systemic sclerosis, and expression of ADAM12 in the dermis, as well as serum levels of soluble ADAM12, is increased in scleroderma patients (89)(90)(91)(92).…”
Section: Skin Fibrosissupporting
confidence: 52%
“…36,37 In fact, the pathogenic link between vascular and fibrotic disease in SSc is still largely unknown and the possible mechanisms associated with the evolution of vascular disease toward fibrotic lesions are, until now, a matter of debate. [38][39][40][41] In our cohort, five patients presented perfusion defect, during stress, in the subendocardial layers, and it is well known that ischemic damage is often confined to the subendocardial layer of the myocardium, as observed in other case series. [28][29][30] In fact, several lines of clinical and experimental evidence suggest that subendocardial muscle is prone to ischemic damage, and physiological mechanisms for this vulnerability, such as the increased subendocardial vessel resistance due to subendocardial systolic compression and the systolic backflow from endocardial to epicardial vessels induced by systolic-diastolic interactions, have been already described.…”
Section: Discussionsupporting
confidence: 68%
“…In fact, the pathogenic link between vascular and fibrotic disease in SSc is still largely unknown and the possible mechanisms associated with the evolution of vascular disease toward fibrotic lesions are, until now, a matter of debate . In our cohort, five patients presented perfusion defect, during stress, in the subendocardial layers, and it is well known that ischemic damage is often confined to the subendocardial layer of the myocardium, as observed in other case series .…”
Section: Discussionmentioning
confidence: 67%